Glycopolypeptide-grafted bioactive polyionic complex vesicles (PICsomes) and their specific polyvalent interactions - Pandey, Bhawana; Mahato, Jaladhar; Cotta, Karishma Berta; Das, Soumen; Sharma, Dharmendar Kumar; Sen Gupta, Sayam; Chowdhury, Arindam (ACS Omega, 2016)
Glycopolypeptide-based self-assembled nano-/microstructures with surface-tethered carbohydrates are excellent mimics of glycoproteins on the cell surface. To expand the broad repertoire of glycopolypeptide-based supramolecular soft structures such as polymersomes formed via self-assembly of amphiphilic polymers, we have developed a new class of polyionic complex vesicles (PICsomes) with glycopolypeptides grafted on the external surface. Oppositely charged hydrophilic block copolymers of glycopolypeptide(20)-b-poly-L-lysine(100) and PEG(2k)-b-poly-L-glutamate(100) [PEG = poly(ethylene glycol)] were synthesized using a combination of ring-opening polymerization of N-carboxyanhydrides and ``click'' chemistry. Under physiological conditions, the catiomer and aniomer self-assemble to form glycopolypeptide-conjugated PICsomes (GP-PICsomes) of micrometer dimensions. Electron and atomic force microscopy suggests a hollow morphology of the PICsomes, with inner aqueous pool (core) and peripheral PIC (shell) regions. Owing to their relatively large (similar to micrometers) size, the hollowness of the supramolecular structure could be established via fluorescence microscopy of single GP-PICsomes, both in solution and under dry conditions, using spatially distributed fluorescent probes. Furthermore, the dynamics of single PICsomes in solution could be imaged in real time, which also allowed us to test for multivalent interactions between PICsomes mediated by a carbohydrate (mannose)-binding protein (lectin, Con-A). The immediate association of several GP-PICsomes in the presence of Con-A and their eventual aggregation to form large insoluble aggregate clusters reveal that upon self-assembly carbohydrate moieties protrude on the outer surface which retains their biochemical activity. Challenge experiments with excess mannose reveal fast deaggregation of GP-PICsomes as opposed to that in the presence of excess galactose, which further establishes the specificity of lectin-mediated polyvalent interactions of the GP-PICsomes.

pH-responsive “supra-amphiphilic” nanoparticles based on homoarginine polypeptides - Praveen, Korra; Das, Soumen; Dhaware, Vinita; Pandey, Bhawana; Mondal, Basudeb; Sengupta, Sayam (ACS Applied Bio Materials, 2019)
pH-responsive “supra-amphiphiles” based on double hydrophilic, positively charged block copolypeptides such as PEG-b-poly-l-lysine together with low molecular weight stimuli-sensitive partners that contain phosphate and carboxylate groups have been widely studied. In contrast, the other widely used cationic polypeptide poly-l-arginine whose cell-penetrating properties are well-known has been much less explored for the synthesis of supra-amphiphile-based nanomaterials. It is also known that the guanidine side chain of arginine binds to carboxylate anions with binding constants that are 2.5 times higher than the corresponding amines of poly-l-lysine. Here, we demonstrate the fabrication of pH-sensitive supra-amphiphilic nanoparticles by simple mixing of PEG2k-b-poly(homoarginine) block copolymer and carboxylic acid containing functional low molecular weight organic compounds. A high yielding three-step methodology was developed for the synthesis of ε-N,N′-di-Boc-l-homoarginine-α-N-carboxyanhydride which was polymerized using amine-terminated PEG (2000 MW) to yield 100% guanine-functionalized polypeptide (PEG2k-b-PHR30) with controlled molecular weights and low PDIs. Incubation of PEG2k-b-PHR30 with four different carboxylic acids (including dexamethasone a glucocorticoid receptor used in cancer therapy) in water leads to the formation of “supra-amphiphilic” nanoparticles (<200 nm size) due to the charge neutralization resulting from the strong interaction between the guanidine group and the carboxylate group. All these nanoparticles were able to encapsulate the hydrophobic dye Nile red with varying efficiency. Although these assemblies were stable at neutral pH, upon lowering the pH of the solution between 4 and 5, the protonation of the carboxylic acids leads to disassembly of these nanoparticles. The cytotoxicity of all four “supra-amphiphilic” nanoparticles varied depending on the carboxylic acid used for their fabrication. While the nanoparticle formed using dioctylbenzoic acid displayed 80% cell viability at concentration of 60 μg/mL, those formed with the steroid deoxycholic acid or dexamethasone showed only 40% cell viability at similar concentrations. Colocalization studies performed using epifluorescence microscopy demonstrate the successful uptake of intact dye-encapsulated nanoparticle inside the cell.

Amphiphilic mannose-6-phosphate glycopolypeptide-based bioactive and responsive self-assembled nanostructures for controlled and targeted lysosomal cargo delivery - Mondal, Basudeb; Pandey, Bhawana; Parekh, Nimisha; Panda, Sidharth; Dutta, Tahiti; Padhy, Abinash; Sen Gupta, Sayam (Biomaterials Science, 2020)
Receptors of carbohydrate mannose-6-phosphate (M6P) are overexpressed in specific cancer cells (such as breast cancer) and are also involved in the trafficking of mannose-6-phosphate labeled proteins exclusively onto lysosomes via cell surface M6P receptor (CI-MPR) mediated endocytosis. Herein, for the first time, mannose-6-phosphate glycopolypeptide ((M6P)GP)-based bioactive and stimuli-responsive nanocarriers are reported. They are selectively taken up via receptor-mediated endocytosis, and trafficked to lysosomes where they are subsequently degraded by pH or enzymes, leading to the release of the cargo inside the lysosomes. Two different amphiphilic M6P block copolymers (M6P)GP(15)-(PPO44)-P-A and (M6P)GP(15)-(PCL25)(2) were synthesized by click reaction of the alkyne end-functionalized (M6P)GP(15) with pH-responsive biocompatible azide end-functionalized acetal PPO and azide end-functionalized branched PCL, respectively. In water, the amphiphilic M6P-glycopolypeptide block copolymers self-assembled into micellar nanostructures, as was evidenced by DLS, TEM, AFM, and fluorescence spectroscopy techniques. These micellar systems were competent to encapsulate the hydrophobic dye rhodamine-B-octadecyl ester, which was used as the model drug. They were stable at physiological pH but were found to disassemble at acidic pH (for (M6P)GP(15)-(PPO44)-P-A) or in the presence of esterase (for (M6P)GP(15)-(PCL25)(2)). These (M6P)GP based micellar nanoparticles can selectively target lysosomes in cancerous cells such as MCF-7 and MDA-MB-231. Finally, we demonstrate the clathrin-mediated endocytic pathway of the native FL-(M6P)GP polymer and RBOE loaded (M6P)GP micellar-nanocarriers, and selective trafficking of MCF-7 and MDA-MB-231 breast cancer cell lysosomes, demonstrating their potential applicability toward receptor-mediated lysosomal cargo delivery.